Anytime information processing based on fuzzy and neural network models - Varkonyi-Koczy, A. R. (2013)
In modern measurement and control systems, the available time and resources are often not only limited, but could change during the operation of the system. In these cases, the so-called anytime algorithms could be used advantageously. While diflerent soft computing methods are wide-spreadly used in system modeling, their usability in these cases are limited.